If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 8x + -1y + -6x + 3 = 0 Reorder the terms: 3 + 8x + -6x + 4y + -1y = 0 Combine like terms: 8x + -6x = 2x 3 + 2x + 4y + -1y = 0 Combine like terms: 4y + -1y = 3y 3 + 2x + 3y = 0 Solving 3 + 2x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 2x + -3 + 3y = 0 + -3 Reorder the terms: 3 + -3 + 2x + 3y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x + 3y = 0 + -3 2x + 3y = 0 + -3 Combine like terms: 0 + -3 = -3 2x + 3y = -3 Add '-3y' to each side of the equation. 2x + 3y + -3y = -3 + -3y Combine like terms: 3y + -3y = 0 2x + 0 = -3 + -3y 2x = -3 + -3y Divide each side by '2'. x = -1.5 + -1.5y Simplifying x = -1.5 + -1.5y
| 2d=7/4 | | x^(3/4)=-9 | | 10+3(4y+2)= | | 93+g=58 | | 0.3(z-10)-0.5z=-6 | | 9-n=7 | | 2r+-82=22 | | 3(5-4x)+2x=65 | | 1/4x-3=-3/4x | | X/9.6=6 | | q/3=-7 | | -6x+9=20-1x | | 3x^4-9x^2+2=0 | | -0.6b=12 | | -23+g=2 | | x+0.15x=28.75 | | .3=35-x*100 x | | -5x-6-6=3 | | x+0.03x=24720 | | W=V-lh | | -6a+5=4a+4 | | (x+7)+(2x+17)=(4x+6) | | 4x^2+16y^2-8x-64y-76=0 | | z^4+6z^3+8z^2=0 | | -2x-5y=4 | | 4x-9=-7x-13 | | -6a+5=4 | | (8*5)+(3*7)=k | | Y=57/14-6 | | (2x+1)+(3x+5)=(6x-6) | | 2x+x=171*2 | | (7x+6)+(4x+14)=(12x+11) |